Analysis User Acceptance of Saudi Banks Applications in Qassim Region Using UTAUT - Almutairi, Bayan S.; Almutairi, Ebtihal K.; Almutairi, Nora M.; Alsheail, Meshaiel M. (Communications in Mathematics and Applications, 2022)
M-Banking is a mobile technology innovation that is compatible with banking financial services. This study aims to determine the factors that affect the customer’s acceptance of using mobile banking services. The UTAUT model was used in this study. The data collection process was carried out through a hard copy and electronic questionnaire through which 318 usable answers were collected from users of mobile banking services in the Qassim region in the Kingdom of Saudi Arabia. The study results indicate that there is a statistically significant relationship between performance expectancy and behavioral intention to use. The results, statistically speaking, demonstrate the factors that affect the customer’s adoption of mobile banking services. The performance expectancy factor was the most influencing factor on the intention to use mobile banking services in Qassim.